Rancang Bangun Aplikasi Sistem Pakar Untuk Menentukan Penyakit Pada Tanaman Kedelai - Wirandha Ryan Pratama; Jusak Jusak; Pantjawati Sudarmaningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2013)
The cause of low yield of soybean in Indonesia, among others is a disease. To find out what disease that attacks soybean crops needed an expert in the field of agriculture. Disease that often impairs the soybean plant is rust. In addition to lowering the yield, rust disease also potentially lower the quality of soybean seeds. In addition to these there are many more diseases that are present in the soy plant. Expert system for soybean disease defines is one alternative to detect disease of soybean. The method used is rule based system and forward chaining method. The system will be made to provide an unbiased decision about the type of disease affecting soybean and handling. Web based system is built in order to spread information more accessible. Result of the application that have been tested by three expert crops by conducting interview and application testing performed eight times on each trial expert. Based on test result obtained from 24 experiments by expert is 22 times the experiment successfully identified soybean disease and two trials did not identify soybean disease. The trial result concluded the expert system can determine soybean disease based on symptoms in plant soybean.